(3eaghe GdCef GdbGfhfj h OhQg aj JTLjY h JfejI GdGSJKeGQ (B/s - (3dWaj, NGdO MSf CMeO s ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2021)
(3aj EWGQ SYj GdOhd Ohd GdYGde fMh YedjI LPH hJTLjY GdGSJKeGQGJ ShGA cGfJ eMdjI Ch CLfHjI, fXQG ddCgejI GdHGdZI dgPg GdCNjQI aj GdbjGe HGdGbJUGO GdhWfj, hOaY YLdI GdJfejI GdGbJUGOjI GdYGdejI(B. (3haj Xd GTJOGO GdefGaSI GdOhdjI fMh LPH GdGSJKeGQ GdCLfHj, CUHM Ydi GdOhd GdeVjaI MJejI JcQjS GdefGN GdbGfhfj GdedGFe ddGSJKeGQ ef NdGd JTQjY GdbhGfjf GdefXeI ddGSJKeGQ hGSJbQGQgG hJaYjdgG hgPG HgOa GdMaGX Ydi fXGe GbJUGOj eJhGRf(B. (3ceG CUHM ef Cge eJWdHGJ GdGSJKeGQ gh JMbjb GdOhdI deHOC GdCef GdbGfhfj, fXQkG deG HdZg ef aYGdjI cHjQI aj LPH GdGSJKeGQGJ GdCLfHjI hjJeKd gPG aj GJMGO GdbQGQ HGdGSJKeGQ aj GdOhdI GdeVjaI dg, h jMOK YcS Pdc aj MGdI GfYOGe GdCef GdbGfhfj dbhGfjf GdGSJKeGQ ajJSHH Pdc aj fahQ GdeSJKeQjf hgPG Hfbd QDhS CehGdge dOhdI eSJbQI bGfhfjkG MjK jJLSO OhQ GdCef GdbGfhfj aj GJNGP GdbQGQ GdGSJKeGQj GdPj jchf Ydi CSGS Jbjje GdeNGWQ GdJj SjhGLghfgG dGMbG, hddCef GdbGfhfj YOI LhGfH efgG eG jJYdb HeHGOF GdeSGhGI hGdMeGjI GdeGdjI hGdbVGFjI GdJj ChQOgG GdeTQY aj Tcd VeGfGJ hMhGaQ hGeJjGRGJ bGfhfjI JefMgG GdOhdI GdeVjaI ddeSJKeQ(B. s
(3HHdjhLQGajG(B: (3U(B. 171-174.s
Keywords: (3GdCef GdbGhfjs; (3GdESJKeGQGJ GdCLfHjI s -- (3bhGfjf h JTQjYGJs -- (3eUQs